2005
DOI: 10.1381/0960892053268453
|View full text |Cite
|
Sign up to set email alerts
|

Fasting Plasma Ghrelin Levels Increase Progressively after Biliopancreatic Diversion: One-year Follow-up

Abstract: Plasma ghrelin levels could be decreased in obese patients as a compensatory mechanism to their nutritional state, but our results do not support the postulated beneficial role of ghrelin in the 1-year weight loss after BPD. They rather suggest that weight loss somehow stimulates ghrelin secretion, even in the absence of part of the stomach.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
1
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(15 citation statements)
references
References 9 publications
1
12
1
1
Order By: Relevance
“…As in other studies [22,23], we were unable to demonstrate a direct association between ghrelin and weight or BMI. Indeed, those patients who underwent RYGB lost the most weight but experienced an increase in ghrelin.…”
Section: Discussioncontrasting
confidence: 91%
See 1 more Smart Citation
“…As in other studies [22,23], we were unable to demonstrate a direct association between ghrelin and weight or BMI. Indeed, those patients who underwent RYGB lost the most weight but experienced an increase in ghrelin.…”
Section: Discussioncontrasting
confidence: 91%
“…We saw that only RYGB was associated with increased ghrelin levels. Others have noted that ghrelin does not vary over the initial months after BPD, with a slight increase at the end of 1 year [20,[22][23][24]. One explanation for this discordance between the results of different studies may involve the differences between the surgical techniques used.…”
Section: Discussionmentioning
confidence: 99%
“…There is general consensus in the literature on increased ghrelin concentrations after weight loss induced by nonsurgical procedures such as low-caloric diet, mixed lifestyle modifications, chronic exercise, cancer anorexia, cardiac cachexia, hepatic cachexia, and anorexia nervosa [41][42][43][44][45]. In contrast, controversial results exist regarding ghrelin concentrations after bariatric surgery: in some studies, ghrelin concentrations increased [46][47][48][49][50], in others decreased [51][52][53], and in others remain stable [54][55][56]. The difference in gastric fundus management in the different bariatric procedures may explain the differences in these results.…”
Section: Discussionmentioning
confidence: 99%
“…However, after the BPD of Scopinaro, fasting plasma ghrelin levels increase [31,36,37], despite reported good weight loss by Scopinaro. Himpens found that, after 3 years following SG, patients have regained their appetite, but their EWL still increased.…”
Section: Presentationsmentioning
confidence: 93%